Emergence of concurrently transmissible mcr-9 and carbapenemase genes in bloodborne colistin-resistant Enterobacter cloacae complex isolated from ICU patients in Kolkata, India - Gourab Halder; Bhaskar Narayan Chaudhury; Priyanka Denny; Mandira Chakraborty; Subhranshu Mandal; Shanta Dutta (Microbiology Spectrum)
ABSTRACT Colistin resistance in carbapenem-resistant Enterobacter cloacae complex (CR-ECC) infections has grown expeditiously but detecting the underlying mechanism of resistance is often challenging in clinical settings. This study, first of its kind from India, determined the resistance mechanisms and characterized colistin-resistant hospital isolates. Twenty-nine bloodborne CR-ECC isolated from ICU patients of eight tertiary care hospitals in Kolkata, India between 2022 and 2023 were screened for colistin resistance. The plasmid-encoded mcr-9 gene, acrAB-tolC efflux pump (EP) & phoP/Q, and pmr A/B two-component system (TCS) involved in colistin resistance were examined. In addition, AMR gene profiling and molecular subtypes of mcr-9-producing CR-ECC isolates were also investigated. All study isolates showed resistance to ≥5 antimicrobial classes and six (21%) of them were colistin-resistant. The mcr-9 gene transferable by IncHI2-HI2A plasmid was detected in both colistin-resistant (67%) and colistin-sensitive (4%) CR-ECC isolates. The blaNDM-5 gene was significantly (P < 0.05) associated with isolates co-harboring mcr-9 genes. A ≥8-fold increase in minimum inhibitory concentration (MIC)colistin was observed in the mcr-9-producing colistin-sensitive strain after induction. Overexpression of acrA, ramA, soxS, phoP/Q, and pmrA/B genes was found in non-mcr-9-producing colistin-resistant isolates. The resistance to colistin in the wild-type appeared to be mediated in part by the mcr-9 gene, an active EP, and regulatory TCS. The mcr-9-producing isolates were typed into ST932, ST270, and ST1997 by MLST. Heterogeneity (29 pulsotypes; 48.40% similarity coefficient) among the circulating CR-ECC isolates was revealed by PFGE. Robust monitoring of mcr genes in both colistin-resistant and -sensitive strains is warranted to curb the menace of AMR in nosocomial pathogens.IMPORTANCECarbapenem-resistant Enterobacter cloacae complex (CR-ECC) has become a global nosocomial pathogen in last few years. Colistin, the “last resort antibiotic,” is being widely used in the treatment of CR-ECC and, consequently, there has been a brisk rise in colistin-resistant CR-ECC isolates. This study was necessitated by the dearth of a comprehensive molecular investigation of colistin-resistant CR-ECC from India. The notorious IncHI2-HI2A plasmid-borne mcr-9 gene along with active acrAB-tolC efflux pump and phoP/Q-pmr A/B two-component system was found to mediate colistin resistance in the study isolates. Interestingly, the mcr-9 gene was also discovered in colistin-sensitive strains and MIC of colistin was found to increase under colistin pressure. Diverse phylogenetic clones along with novel sequence types were detected. This study highlights the necessity for intense monitoring of mcr-9 in conjunction with the existing epidemic clones of CR-ECC strains harboring diverse arrays of transmissible AMR genes.